Antimicrobial and Metal Resistance Genes in Bacteria Isolated from Mine Water in Austria - Jakob Prochaska (Antibiotics, 2025)
Background/Objectives: Microbiomes surrounding mining sites have been found to harbor both antibiotic resistance genes and metal resistance genes. Within the “One Health” framework, which spans human, veterinary and environmental health, it is crucial to determine whether bacterial metal resistance (MR) genes can independently trigger antimicrobial resistance (AMR) or if they are linked to AMR genes and co-transferred horizontally. Methods and Results: Bacteria were isolated from an active and an inactive mining site in the alpine region of Austria. Most of the isolated bacteria harbored antimicrobial and metal resistance genes (88%). MALDI-TOF and whole genome sequencing (WGS) revealed that species from the Pseudomonadaceae family were the most identified, accounting for 32.5%. All Pseudomonas spp. carried AMR genes from the mex family, which encode multidrug efflux pumps. β-lactamase production encoded by bla genes were detected as the second most common (26%). The same AMR genes have often been detected within a particular bacterial genus. No tetracycline resistance gene has been identified. Among metal resistance genes, rufB (tellurium resistance) was the most prevalent (33%), followed by recGM (selenium resistance, 30%), copA (copper resistance, 26%), and mgtA (magnesium and cobalt resistance, 26%). Notably, the mer gene family (mercury resistance) was found exclusively in isolates from the inactive mining site (n = 6). In addition, genes associated with both antimicrobial and metal resistance, including arsBM, acrD, and the mer operon, were identified in 19 out of the 43 isolates. Conclusions: Bacteria isolated from mine water harbored both MR and AMR genes. Given the exceptional diversity of bacterial species in these settings, 16S rRNA gene sequence analysis is the recommended method for accurate species identification. Moreover, the presence of multi-drug transporters and transferable resistance genes against critically important antimicrobials such as fluoroquinolones and colistin identified in these environmental bacteria emphasizes the importance of retrieving environmental data within the “One Health” framework.